Appraisal of the Role of Legal Research Assistant to Judges in the Nigerian Judicial Sector - Fasuyi, Precious; Fatoki, Yewande; Godwill, Okpoi Elade-Ebi (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
Judicial or legal research assistants play a vital role in the process of adjudication. The judicial assistants or research assistants are persons who carry out research on legal topics and lend assistance in whatever ways possible for the Judges. They are in a position of trusted agents of a Judge. This paper stems from the fundamental problem that little is known about the role and duties of the legal research assistant as they work with the judges behind the scene and not all courts have embraced the judicial assistant and also there is the lack of regulatory framework guiding the research assistants in the course of their duty. The aim of this paper is to consider the important role the legal research assistant plays in the administration of justice and decision-making in Nigeria notwithstanding the introduction of Artificial Intelligence in the 21st Century. The paper adopts the Doctrinal method of legal research. The paper finds that the research or judicial assistant have not been totally embraced by all courts in Nigeria and there is no law in existence which spells out the power, duties or regulation to guide research assistants in the course of their duties. Hence, their scopes of duties are not defined. The paper concludes that the position of a legal research assistant is not holistically recognized under the Nigerian judicial system and recommends that the judiciary needs to embrace the use of judicial research assistant for the overall improvement and more efficient decision making process of the justice sector in Nigeria.